(Ca, Sr, Ba)ZrO3: A promising entropy-stabilized ceramic for titanium alloys smelting. (28th February 2021) - Qiu, Shuaihang; Li, Mingliang; Shao, Gang; Wang, Hailong; Zhu, Jinpeng; Liu, Wen; Fan, Bingbing; Xu, Hongliang; Lu, Hongxia; Zhou, Yanchun; Zhang, Rui
Abstract: A novel entropy-stabilized (ES) (Ca, Sr, Ba)ZrO3 ceramic has been designed and synthesized by pressureless sintering of CaZrO3, SrZrO3 and BaZrO3 powders mixtures at 1450 °C, 1500 °C and 1550 °C for 3 h. X-ray diffraction, scanning electron microscopy and transmission electron microscopy analyses collectively indicate that a single solid solution is formed with a homogeneous distribution of metal elements after sintering at 1550 °C. The relative density and hardness of the ES (Ca, Sr, Ba)ZrO3 ceramic sintered at 1550 °C are 97.79 % and 10.84 ± 0.33 GPa, respectively. This ES (Ca, Sr, Ba)ZrO3 exhibits lower thermal conductivity from 373 K to 1073 K than their constituting zirconates, CaZrO3, SrZrO3 and BaZrO3 . Most importantly, the ES (Ca, Sr, Ba)ZrO3 ceramic possesses good corrosion resistance to TiNi alloy melt and no distinct reaction layer exists between TiNi alloy and ES (Ca, Sr, Ba)ZrO3 ceramic in the contact region. The combination of these properties indicates that ES (Ca, Sr, Ba)ZrO3 ceramic is promising for use as a novel crucible material for the melting of titanium alloys.